Acid hydrolysis of Solanum tuberosum periderm for accumulation of polyhydroxyalkanoates in Pseudomonas putida MTCC 2475 - Kag, Sonika; Kumar, Pravir; Kataria, Rashmi (Frontiers in Bioengineering and Biotechnology, 2024)
Polyhydroxyalkanoates are a class of biodegradable, biocompatible polymers composed of polyesters of R-hydroxyalkanoic acids and deposited intracellularly by a variety of microorganisms which have potential to serve as alternative to commercial plastic. Bioplastics are gaining attention due to sustainability, biodegradability, biocompatibility, and lower carbon footprint. Nevertheless, the commercialization of PHA is predominantly hindered by the elevated production expenses arising primarily from the use of a pure sugar substrate. Our study has established a feasible method for bioplastic formation applying Pseudomonas putida MTCC 2475 and Solanum tuberosum periderm as a carbon source. To optimize the sugar yield response surface methodology was used, which released 69.34 ± 0.25% reducing sugar. PHA production experiments were performed in hydrolysate containing media as well as commercial sugar containing mineral salt media. After 48 hours of fermentation of using this sugar, a biomass concentration of 2.19 gL -1 , with a PHA production of 0.60 gL -1 (28.71 ± 0.55%) was obtained which was comparatively similar with synthetic media (2.56 gL -1 cell dry weight and 29.97 ± 0.45% PHA). Furthermore, the monomers of PHA produced by hydrolysate were characterized using Gas chromatography-mass spectrometry, Fourier transform infrared spectroscopy, differential scanning calorimetry, and nuclear magnetic resonance. This investigation has identified three distinct monomers of medium-chain PHAs, namely, methyl 3-Hydroxydodecanoate, 3-Hydroxytetradecanoate, and Hexadecanoic acid 3-Hydroxy methyl esters.Hence this study concludes a sustainable production of bioplastics from S. tuberosum periderm waste.